Interpretasi Kritik Arsitektur Pada Bangunan Bergaya Kolonial Belanda “Notariskantoor Bojonegoro” Dengan Metode Kritik Normatif, Interpretatif, dan Deskriptif - Ine Distiana Rohmadhoni; Dhiah Agustina Qahar; Aktur Ali Shodikin (Sustainable Civil Building Management and Engineering Journal, 2025)
Buildings that are unique and different from most of the buildings around them can be striking and attract attention, besides this difference in design can also become branding and a landmark for the area. This can also be seen in the unique Notaris Kantoor building located in Bojonegoro Regency, so the aim of making this building an object of criticism is to introduce the design of this building to the general public to use as design inspiration and break the negative stigma about the building in question. The criticism methods used are normative criticism, interpretive criticism and descriptive criticism. Normatively, this building is a new building that was deliberately designed with a Dutch colonial concept, the choice of shape, materials and colors gives a calm impression so that it is easy to remember as an iconic place in the Bojonegoro area. Interpretatively, this building might give rise to a different perspective from the public towards the building owner who considers the owner of this building to have a high RAS and social strata. However, despite this, this building still fits in the area and has a distinctive characteristic in the minds of the people. Descriptively, this building has 2 viewpoints from which you can enjoy its beauty because it is located in the corner area of ​​a T-junction so the view is not disturbed by other buildings and choosing the right materials makes this building have more aesthetic value. Based on the results of this criticism, it can be concluded that the Notaris Kantoor building has a unique and striking Dutch colonial design style. The choice of location, color, ornaments and materials is very precise, giving the impression that it is not excessive so that the negative stigma about building designs that are considered haunted and related to the owner's RAS can be broken.